Frontal plane knee displacement in barbell back squat - Bailey, C. A.; Sato, K.; Heise, G. D. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of the study was to analyze the ML knee displacement and its influence on barbell tilt and rotation displacement from the back squat. Based on the weight distribution (WtD) test, 13 were in the equal WtD group and 14 were in the unequal WtD group. All subjects performed 75% of 1RM barbell back squat with reflective markers on selected locations for motion analysis. Medial-lateral (ML) knee displacement, barbell tilt and rotation displacements were considered. The results showed a statistically significant difference between groups (p<0.01), but no significant difference in ML knee displacement of the left and right sides (p=0.63). There were no correlations between ML knee displacement asymmetry and barbell tilt (p=0.12) and rotational displacement (p=0.07), indicating frontal knee action may not explain unwanted barbell movements in back squat.